Envisioning the future with ‘compassionate conservation’: An ominous projection for native wildlife and biodiversity - Callen, A; Hayward, M; Klop-Toker, K; Allen, B; Ballard, G; Broekhuis, F; Clarke, R; Clulow, J; Clulow, S; Daltry, J; Davies-Mostert, H; Di Blanco, Y; et al. (Elsevier, 2019)
The ‘Compassionate Conservation’ movement is gaining momentum through its promotion of ‘ethical’ conservation practices based on self-proclaimed principles of ‘first-do-no-harm’ and ‘individuals matter’. We argue that the tenets of ‘Compassionate Conservation’ are ideological - that is, they are not scientifically proven to improve conservation outcomes, yet are critical of the current methods that do. In this paper we envision a future with ‘Compassionate Conservation’ and predict how this might affect global biodiversity conservation. Taken literally, ‘Compassionate Conservation’ will deny current conservation practices such as captive breeding, introduced species control, biocontrol, conservation fencing, translocation, contraception, disease control and genetic introgression. Five mainstream conservation practices are used to illustrate the far-reaching and dire consequences for global biodiversity if governed by ‘Compassionate Conservation’. We acknowledge the important role of animal welfare science in conservation practices but argue that ‘Compassionate Conservation’ aligns more closely with animal liberation principles protecting individuals over populations. Ultimately we fear that a world of ‘Compassionate Conservation’ could stymie the global conservation efforts required to meet international biodiversity targets derived from evidenced based practice, such as the Aichi targets developed by the Convention on Biological Diversity and adopted by the International Union for the Conservation of Nature and the United Nations.